Marijuana on the Mind? The Impact of Marijuana on Cognition, Brain Structure, and Brain Function, and Related Public Policy Implications. (March 2017) - Gruber, Staci A.; Sagar, Kelly A.
Although marijuana (MJ) has been used for thousands of years, the public's opinion of MJ has shifted drastically over the past century, leaving many wondering about its potential risks and benefits. This article summarizes research detailing the impact of recreational MJ and related variables (frequency, magnitude, potency, and mode of MJ use) on cognition, brain structure, and brain function. MJ use, particularly at young ages, has been reported to undermine cognition, as well as alter brain structure and function. Furthermore, we discuss how data from recreational MJ studies, as well as more recent medical marijuana (MMJ) research findings, relate to legalization efforts. Considerations for policymakers, such as age limits, guidelines for safe use, and the therapeutic potential of certain constituents of MJ (i.e., cannabidiol), are also outlined. In recent years, policy has outpaced science; important areas in need of further research are noted.